(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction:Mandible, a bone well known since decades for determination of age and sex in an individual among forensic experts, possesses coronoid process, a triangular flat piece of bone projecting anteriorly in the upper part of ramus of mandible. This process depicts variations in shapes due to attachments of muscles of mastication. Aim of study: Evaluation of incidence in shape of coronoid process along with variation amongst gender and sides of mandible within a given sample. Materials and Methods: A total of 125 adult human dry mandibles (i.e.,250 coronoid process); both male and female; collected from Department of Anatomy and Department of Forensic Medicine at Subharti Medical College, Swami Vivekanand Subharti University, Meerut were studied and analysed.